Multi-core computer vision and image processing for intelligent applications - Mohan S.; Vani V. (Advances in computational intelligence and robotics (ACIR) book series, 2017)
This book is an essential publication outlining the future research opportunities and emerging technologies in the field of image processing, and the ways multi-core processing can further the field.